TRANSFER PRICING PRACTICE ON TAX AVOIDANCE AND TAX REVENUE : A BIBLIOMETRIC ANALYSIS - Islam, Alifia Izzah; Tjaraka , Heru (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
Tax avoidance taken by companies can cause tax revenue for the state to be optional. One of the factors that influences tax avoidance is transfer pricing practices. Transfer pricing is determining prices in transactions between businesses with common ownership and control. Transfer pricing determines the prices and services exchanged between related entities, especially subsidiaries and multinational companies. This study is to assess the practice of transfer pricing on tax revenue and tax avoidance. This is different from previous research because previous studies only discussed tax expenditures; this research discusses other topics, namely transfer pricing, tax avoidance, and tax avoidance. The present study employed data extracted from the Google Scholar database with articles published between 2019 and 2023 using the keywords “transfer pricing," “tax avoidance," “multinational corporate," and “tax revenue." Only the title, abstract, and keywords were searched. The results of bibliographic aggregation analysis using the VOSviewer application resulted in 3 clusters. This research highlights the importance of using bibliometric tools such as VOSviewer to understand trends and relationships in academic literature. The results of this bibliometric analysis have several important implications for research and policy. The findings show growing attention to environmental issues in the context of tax policy, as indicated by the increasing literature on carbon taxes and pricing.